The Use of the Arm Circumference as a Measure to Detect Underweight in Individuals Aged 60 Years or Older Living in Costa Rica - Aguilar-Fernández, Eduardo (2023)
[Objective]: This investigation focuses on the association between arm circumference and body mass index, and the estimation of cutoff values of this arm measurement for identifying low weight in Costa Rican residents aged 60 years and over. [Methods]: The study included a total of 2514 persons 60 years old or older who participated in the project “Costa Rica: Study of Longevity and Healthy Aging.” The analysis included calculation of Spearman’s correlation coefficient between arm circumference and the body mass index, the area under the Receiver Operating Characteristic (ROC) curve, and sensitivity and specificity values for measurements of arm circumference corresponding to a body mass index lower than 22 kg/m2. [Results]: The Spearman’s correlation coefficient between the body mass index and the arm circumference was 0.794 (0.774 for men and 0.806 for women). The optimum cutoff point was estimated at 26.5 cm, with a Youden’s Index of 0.7256, a sensitivity of 87.79 %, and a specificity of 84.77 %. Specific cutoff points for men and women were 26.5 cm and 25.9 cm, respectively. [Conclusions]: There is a strong relationship between arm circumference and body mass index in Costa Rican residents aged 60 years and over. A first approach was established to determine an adequate cutoff point in the measurement of arm circumference that will allow the detection of persons with low weight and greater nutritional risk in this population.